Efficacy and Safety of Low-Doses of Botulinum Toxin Type-A in the Treatment of Primary Axillary Hyperhidrosis over 6 Months - Nisreen Darwish; Abdel Haleem Romieh; Mahmoud Dalloul (Journal of King Abdulaziz University: Medical Sciences, 2023)
Primary axillary hyperhidrosis is a relatively common benign disease that has a negative impact on the patient’s quality of life. Although primary axillary hyperhidrosis has readily been treated with standard doses of botulinum toxin type A, the efficacy of low-doses is not well established. The efficacy and safety of low-doses of botulinum toxin type A in the treatment of primary axillary hyperhidrosis over 6 months was evaluated. A randomized comparative side was performed-by side study in twenty-one patients treated with one course of botulinum toxin type A (Relife®), divided into 50 units injected in the right axilla and 25 units injected in the left axilla. Sweating was evaluated by minor iodine-starch test at weeks 1-4-16-24. The low-dose efficacy average was 100%, 90.48%, 80.95%, 71.43% at weeks 1-4-16-24, respectively; compared to standard-dose efficacy average of 100%, 95.24%, 90.48%, and 76.19% at weeks 1-4-16-24, respectively. Statistically, no significant differences in the efficacy of the two doses of botulinum toxin type A were found. Minor adverse effects were demonstrated in 33% of patients, thus, recovered completely with no need for medication. In conclusion, these results suggest that low dose of botulinum toxin typeA is safe, effective and a well-tolerated treatment for axillary hyperhidrosis, and its benefits last for at 6 months.